An alternative approach to the monetary mechanism - United States; United States (Washington : U.S. Govt. Print. Off., 1964)
This book contains the report of the Subcommittee on Domestic Finance, Committee on Banking and Currency, House of Representatives, 88th Congress, on an alternative approach to monetary mechanism. 2d sess., Aug. 17, 1964.
usc 24/08/2018
Ref
Keywords: Federal Reserve banks; Monetary policy; United States